PROFILE OF PATIENTS WITH URINARY INCONTINENCE IN A UNIVERSITY HOSPITAL OUTPATIENT CLINIC (Estima – Brazilian Journal of Enterostomal Therapy, 2021)
Objective: to know the sociodemographic and clinical profile of people with urinary incontinence in an outpatient clinic of a University Hospital. Methods: cross-sectional study, using a semi-structured form with 63 women whowere awaiting care at the gynecology and urology outpatient clinics, between the months of July and August 2019. The data were processed in the software Statistical Package for the Social Sciences – SPSS 20.0. Results: interviews were carried out with women aged between 19 and 77 years. Of these, 55.6% maintained an active sex life; 85.7% had pre-existing disease; 69.8% presented urinary loss when coughing, sneezing, smiling, putting on weight and/or making efforts; 12.7% need to urinate as soon as they feel like it; and 17.5% had loss of urine in both situations. About 35% sought consultation due to low bladder and/or loss of urine; 27% had 4 to 5 pregnancies. Among the risk factors associated with urinary incontinence, 28.6% had diabetes mellitus, 61.9% had arterial hypertension, 82.5% used continuous medication, 11.1% was obese, 34.9% reported constipation problems and 74.6% underwent pelvic surgery. Conclusion: it was concluded that all women in the study had more than one risk factor for developing urinary incontinence, reinforcing their multifactoriality, as well as the importance of a holistic and multiprofessional treatment.